David Murray: the making of a progressive musician - Wall, Tim (Jazz Research Journal, 2008)
David Murray has been a leading innovative jazz musician for the last thirty years. He has been a prolific recording artist and concert performer, and an eclectic collaborator within and outside the jazz tradition. This paper explores the cultural and political economic context in which he works as a professional musician and in which his work is listened to and understood. Reinterpreting Scott DeVeaux’s notion of the ‘progressive musician’, Murray’s work is discussed in terms of the venues, record companies and wider media in which he performs, and the different ways in which ideas of progress have both changed over time, and been interpreted in the US and UK. It also explores the important role of critic Stanley Crouch in the development of Murray’s career and the wider critical context in which the meanings and value of jazz are discussed. The analysis is based upon a historiography of Murray’s career and recorded output and an examination of original press coverage and primary interviews with key music industry personnel. Conclusions are drawn about distinctly different European and African American ideas of progress and tradition in jazz, and about the infrastructure that sustains working jazz musicians.